Environmental Characteristics of Slum Settlements in Batang Arau Village of Padang City - Aziz, Rizki -; Noer, Melinda; Risna, Lisa (Indonesian Journal of Environmental Management and Sustainability, 2019)
In order to comprehend the problems of slums comprehensively, knowledge of the environmental characteristics of slums is needed based on the classification of aspects of facilities, infrastructure, social, economic, and disaster (hazard). This study aims to understand the characteristics of the environment in the form of infrastructure, social, economic, and slum disasters in the Batang Arau Village, Padang City. Primary data were obtained through field observations and interviews with 80 informants, while secondary data obtained from related documents and regulations. The physical condition of the area is that the regularity of residential buildings is only 102 units of households with the level of regularity of buildings, only 0.26%. The level of residential building density of 522.36 units / Ha, with the feasibility of residential buildings, is only 0.76%. Accessibility following technical requirements is only 0.40%. The condition of the drainage network that meets the minimum quality standard is 0.19%. The number of houses served with water facilities for basic needs of 0.58% with the fulfillment of 0.47%. The percentage of family latrines according to technical requirements of 0.41%, and the amount of domestic household waste that is transported at least twice a week is 49%. Socially, the number of people by sex is almost the same, with the distribution of the productive age of the population of 69.32% of the total population, the level of education varies but in general is high school education, and the most dominant ethnic group in this area is the Minangkabau. From an economic aspect, people's income varies, with work predominantly being fishermen and trade/services. This area is located on a hillside, making it prone to landslides, and due to dense houses, this area is also prone to fires.